2020
DOI: 10.1186/s12871-020-01039-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects and mechanisms of local anesthetics on esophageal carcinoma cell migration, growth, survival and chemosensitivity

Abstract: Background: Retrospective analysis and pre-clinical studies suggest that local anesthetics have anti-tumoral effects. However, the association between cancer recurrence and the use of local anesthesia is inconclusive and most reports are based on single local anesthetic results. Methods: The biological effects (growth, migration and survival) of four common local anesthetics on esophageal carcinoma cells were compared. Biochemical assays on molecules involved in cell migration and proliferation were analyzed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…The amide type LAs bupivacaine and lidocaine are on the WHO's list of essential drugs 9,10 and may also have antitumor effects for several tumor entities. 11,12 Furthermore, a recent study by Tohme et al observed that neutrophil extracellular traps (NETs), which are chromatin DNA released by PMNs, were implicated in colorectal carcinoma liver metastasis after surgical stress. 13 Galos et al could observe reduced NETosis in women treated with intravenous lidocaine during breast cancer surgery which might result in lower recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
“…The amide type LAs bupivacaine and lidocaine are on the WHO's list of essential drugs 9,10 and may also have antitumor effects for several tumor entities. 11,12 Furthermore, a recent study by Tohme et al observed that neutrophil extracellular traps (NETs), which are chromatin DNA released by PMNs, were implicated in colorectal carcinoma liver metastasis after surgical stress. 13 Galos et al could observe reduced NETosis in women treated with intravenous lidocaine during breast cancer surgery which might result in lower recurrence rates.…”
Section: Introductionmentioning
confidence: 99%
“…This study suggested that by administering topically within the oral cavity, lidocaine cold suppress the proliferation of human tongue cancer cells ( Sakaguchi et al, 2006 ). A recent study also confirmed the suppressing effects of lidocaine to the cell migration, growth, and survival of esophageal carcinoma at >100 μM, which was mediated by inhibiting mitochondrial respiration ( Zhu et al, 2020 ).…”
Section: Lidocaine In Cancer Treatmentmentioning
confidence: 73%
“…There is also research showing that under clinically relevant concentrations (0.1–200 μM), lidocaine exhibited anticancer efficacies. The plasma concentration of local anesthetics is at low μ M, ranged from 2.5–10 μM, suggesting a suitable administrative method, such as local infiltration or administering topically, should be taken into account when used for killing cancer cells ( Li R. et al, 2018 ; Zhu et al, 2020 ). More efforts, including the pharmacokinetics profile in vivo, are needed to verify its campatibal dose/concentration in certain treatments that are achievable in clinical practice.…”
Section: Discussion and Future Perspectivesmentioning
confidence: 99%
“…Although early small retrospective clinical trials have shown that local anesthetics play a beneficial role in reducing tumor metastasis and recurrence in cancer patients, prospective, large-scale, and randomized clinical trials are needed to investigate the effect of regional anesthesia on long-term outcomes after cancer surgery [37]. This will confirm the significance of anesthetics for cancer patients and guide clinical practice.…”
Section: Discussionmentioning
confidence: 99%